Análisis jurídico de la tauromaquia en el Ecuador - Ordóñez Córdova, Andrés Danilo (2009)
The present titillation work, embrace a study of the legality and protection of bull fighting activity in Ecuador, due to the current anti-taurine tendencies of protest and requests which don’t attach to the national legislation, analyzing if is viable or not the bull fighting prohibition according to the direct or indirect rights and laws that enrolls the mentioned activity, studying the national legislation, cultural environment, and the custom which precedes the “fiesta brava”, to evaluate if certain legal protection exists or should exist about this show, considering as an criticized art because of disowned or anti – taurine mitts. Considering this is a polemical topic, it should be analyzed how bull fighting activity is or should be regulated by the law, in order to guarantee the juridical safety and the legality of “Fiesta Brava” in our country, in virtue of the rights that embrace this activity. A complete study must be made, about how the current anti – taurine protests affects to the legislation from the juridical perspective, due to the fact that art of bull fighting represents a strong found of ingresses in several sectors of the country, as well as the correlative obligations and rights that come out of this activity.